The Cardiovascular Effect of Systemic Homocysteine Is Associated with Oxidative Stress in the Rostral Ventrolateral Medulla - Zhong, Mei-Fang (Neural Plast, 2017)
It has been demonstrated that homocysteine (HCY) is a significant risk factor of hypertension, which is characterized by overactivity of sympathetic tone. Excessive oxidative stress in the rostral ventrolateral medulla (RVLM), a key region for control of sympathetic outflow, contributes to sympathetic hyperactivity in hypertension. Therefore, the goal of the present study is to determine the effect of systemic HCY on production of reactive oxygen species (ROS) in the RVLM. In the rat model of the diet-induced hyperhomocysteinemia (L-methionine, 1 g/kg/day, 8 weeks), we found that the HCY resulted in a significant increase (≈3.7-fold, P < 0.05) in ROS production in the RVLM, which was paralleled with enhanced sympathetic tone and blood pressure (BP). Compared to the vehicle group, levels of BP and basal renal sympathetic nerve activity in the HCY group were significantly (P < 0.05, n = 5) increased by an average of 27 mmHg and 31%, respectively. Furthermore, the rats treated with L-methionine (1 g/kg/day, 8 weeks) showed an upregulation of NADPHase (NOX4) protein expression and a downregulation of superoxide dismutase protein expression in the RVLM. The current data suggest that central oxidative stress induced by systemic HCY plays an important role in hypertension-associated sympathetic overactivity.